Who has the better story? On the narrative foundations of agricultural development dichotomies. (November 2020) - Mockshell, Jonathan; Birner, Regina
Highlights: Analyzing narratives is important but has been neglected in agricultural policy analysis. We combine the Advocacy Coalition Framework with Narrative Policy Analysis. We identified two advocacy coalitions, reflecting a dichotomy in perspectives. One tells straightforward stories, while the other one formulates mostly critiques. Successful meta-narratives, which could bridge the dichotomy, are yet to be developed. Abstract: While there is consensus on the need to promote agricultural development in Africa to achieve food security and use agriculture as an engine of growth, there is a lively policy debate on appropriate policies to achieve this goal. In the past two decades, there has been a revival of policies that favor government support to agriculture in Africa, especially in the form of input subsidies. Such policies have remained highly controversial, reflecting a long-standing dichotomy in agricultural development policy between those who consider subsidies as essential to increase agricultural productivity and those who criticize such state-focused policy instruments and favor market-oriented approaches. In the literature, agricultural policy choices have mainly been analyzed using models that capture economic or political interests. Some studies have focused on policy beliefs to explain the dichotomy, but what has not received much attention is the use of language in agricultural policy discourses, in spite of increasing evidence that narratives matter for policy-making. To address this gap, we combine the Advocacy Coalition Framework with Narrative Policy Analysis to examine agricultural policy discourses in Senegal. Applying a cluster analysis to coded transcripts of in-depth interviews with policy stakeholders, we identified two opposing advocacy coalitions and labelled them "agricultural support coalition" and an "agricultural support critique coalition". An analysis of the argumentative structure of the narratives of each coalition revealed interesting differences: while the agricultural support coalition told a range of straight-forward stories that explain how government support, such as input subsidies, addresses the problem of low agricultural productivity, the opposing coalition formulated their stories mostly in the form of critiques rather than telling equally straight-forward counter-stories. Based on the analysis, we examine possible meta -narratives, which take arguments of both coalitions into account and may have the potential to overcome the long-standing dichotomy in agricultural development.